Mixed Lineage Kinase Phosphorylates Transcription Factor E47 and Inhibits TrkB Expression to Link Neuronal Death and Survival Pathways - Pedraza, Neus (American Society for Biochemistry and Molecular Biology, 2009)
E47 is a basic helix-loop-helix transcription factor involved in neuronal differentiation and survival. We had previously shown that the basic helix-loop-helix protein E47 binds to E-box sequences within the promoter of the TrkB gene and activates its transcription. Proper expression of the TrkB receptor plays a key role in development and function of the vertebrate nervous system, and altered levels of TrkB have been associated with important human diseases. Here we show that E47 interacts with MLK2, a mixed lineage kinase (MLK) involved in JNK-mediated activation of programmed cell death. MLK2 enhances phosphorylation of the AD2 activation domain of E47 in vivo in a JNK-independent manner and phosphorylates in vitro defined serine and threonine residues within a loop-helix structure of AD2 that also contains a putative MLK docking site. Although these residues are essential for MLK2-mediated inactivation of E47, inhibition of MLKs by CEP11004 causes up-regulation of TrkB at a transcriptional level in cerebellar granule neurons and differentiating neuroblastoma cells. These findings allow us to propose a novel mechanism by which MLK regulates TrkB expression through phosphorylation of an activation domain of E47. This molecular link would explain why MLK inhibitors not only prevent activation of cell death processes but also enhance cell survival signaling as a key aspect of their neuroprotective potential.